ENHANCING LOCAL REVENUE THROUGH MANAGEMENT CONTROL SYSTEMS: A CASE STUDY OF THE BANTUL TOURISM OFFICE - Winda Ryzka; Athallah, Fadel Zaidan; Utomo, Erliana F.A; Putra, Adrew Marcelo (INSTITUT TEKNOLOGI DAN BISNIS PGRI DEWANTARA JOMBANG, 2026)
The management of tourism levies constitutes an important issue in the optimization of Local Own-Source Revenue, particularly in destinations with high visitor volumes such as Parangtritis Beach in Bantul Regency. This study aims to analyze potential control gaps in the management of tourism levies through the Management Control Systems and Government Internal Control System frameworks. It employs a qualitative library-based approach using secondary data in the form of regulations, government documents, public statistics, and other relevant supporting sources. The findings indicate limitations in access control, the integration of visitor and revenue data, the visibility of staff performance evaluation, and the strengthening of compliance as part of cultural controls. These findings suggest that problems in tourism levy management are not merely technical, but are also related to the design and interconnection of action controls, results controls, personnel controls, and cultural controls. The study concludes that strengthening operational controls, information systems, data-based evaluation, and accountability values is necessary to support more reliable and accountable tourism levy management. The implication is that local governments need to position levies as a governance issue rather than merely an administrative revenue matter